Genetic evidence supports polygamous mating system in a wild population of Prochilodus lineatus (Characiformes: Prochilodontidae), a Neotropical shoal spawner fish - Ribolli, Josiane (2020)
Behavioral observations made on fish have revealed remarkably diverse reproductive strategies, including polygamy by both sexes. Still, to date, most Neotropical species remain unstudied as to whether the observed reproductive behavior in natural populations correlates with their genetic mating systems. Here, we investigated the genetic mating system of a wild population of Prochilodus lineatus settled in the Middle Uruguay River basin. By using sibship reconstruction and parental inference methods based on microsatellites? genotypes, we inferred 45 females and 47 males as potential parents of the 87 larvae analyzed. We found evidence supporting polygamous mating in both sexes: while a high percentage of males (44.7%) fertilized the eggs of one female, 55.3% of the inferred males fertilized eggs of up to four females. Likewise, while 44.5% of the inferred females had their eggs fertilized by one only male, 55.5% of females were fertilized by multiple males. The estimated proxy of the effective population size (Nb) was 126, exhibiting moderate to high levels of genetic diversity. The genetic evidence contributed in this study complements earlier behavioral observations of formation of spawning nuclei of aggregating breeders, which may be promoting a polygamous mating strategy in this long-distance migratory fish.